Irrigation Deficit for Ciherang Rice Variety as a Benchmark for Developing Upland Rice Cultivation Systems - Sri Widata; Zamroni Zamroni; Driska Arnanto; Darnawi Darnawi; Ahmad Ferry Baharudin; Yunianta Yunianta; Ignatius Suprih Sudrajat (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study aims to evaluate the agronomic response of Ciherang rice plants during the vegetative and generative phases under deficit irigation conditions, as a benchmark for cultivation in dry land. This study used a factorial Completely Randomized Design with two factors. First, the level of water efficiency consisting of three levels, namely 300 ml, 600 ml, and 900 ml; second, the ratio of cattle manure and urea fertilizer also consisting of three levels, namely 80:20, 50:50, and 20:80. The observed variables include vegetative phase parameters, such as plant height, number of tillers, and dry weight of biomass, as well as generative phase parameters, such as percentage of filled grains and weight of filled grains per clump. The results showed that there was a significant interaction between water efficiency and fertilizer ratio during the generative phase, but no similar interaction was found during the vegetative phase. Furthermore, the combination of 600 ml water treatment with a 50:50 fertilizer ratio produced the highest percentage of filled grains and weight of filled grains. These results indicate that Ciherang rice can grow well under efficient water conditions, making it potentially suitable for cultivation in dry land.